Variability of competition-based caloric expenditure and relative heart rates in National Collegiate Athletic Association Division I women's basketball - Sanders, G. J.; Boos, B.; Rhodes, J.; Peacock, C. A.; Kollock, R. O.; Scheadler, C. M. (The Journal of Strength and Conditioning Research, 2022)
Basketball athletes frequently engage in high intensities (=85% HRpeak) throughout competition, and it is unknown how high-intensity play coincides with caloric expenditure and average and peak relative heart rates. The purpose of the study was to assess caloric expenditure throughout 31 games (4- to 10-minute quarters) in National Collegiate Athletic Association Division I women's basketball. A total of 11 female athletes were tested for peak heart rate (HRpeak) and peak oxygen uptake (Vo2peak) before the season, then monitored in-season with heart rate-based wearable devices. Estimated caloric expenditure, average (% HRavg) and peak (% HRpeak) relative heart rates, time played at intensities =85% HRpeak, and live time (i.e., game minutes not including stoppages in play) were recorded each game. Data were assessed as a team and compared across 4 quarters, and then, interathlete comparisons were made based on full game data. There were significant main effects of 10-minute quarters on calories (p < 0.001) and % HRavg (p = 0.015) but not playing intensity =85% HRpeak (p = 0.125) and % HRpeak (p = 0.629). Caloric expenditure was the only variable to increase from the first to the fourth quarter. There were main effects of individual athletes on calories, % HRavg, % HRpeak, live time, and playing intensity =85% HRpeak (p < 0.001 for all). Assessing individual athletes, relative to a team assessment across quarters, can provide practitioners with more accurate caloric expenditure, heart rate, and playing intensity data per athlete to improve training and fueling protocols.